2017
DOI: 10.1007/s00431-017-2866-3
|View full text |Cite
|
Sign up to set email alerts
|

Crossover study of assist control ventilation and neurally adjusted ventilatory assist

Abstract: NAVA compared to ACV improved oxygenation in prematurely born infants with evolving or established BPD. What is Known: • Neurally assist ventilator adjust (NAVA) uses the electrical activity of the diaphragm to servo control the applied pressure. • In infants with acute RDS, use of NAVA was associated with lower peak inflation pressures and higher tidal volumes. What is New: • This study uniquely reports infants with evolving or established BPD, and their results were compared on 1 h each of NAVA and assist co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 13 publications
2
27
0
3
Order By: Relevance
“…A sample size of 18 infants was chosen as this would allow detection of one standardised difference in the results with 80% power at the 5% significance level. In a previous study [14], we reported a difference in the mean OI of infants supported by NAVA compared to ACV was greater than 3 with a standard deviation of the infants' results being 2. We had also reported a difference of 3 in previous studies of PAV [6,8].…”
Section: Sample Sizementioning
confidence: 71%
See 1 more Smart Citation
“…A sample size of 18 infants was chosen as this would allow detection of one standardised difference in the results with 80% power at the 5% significance level. In a previous study [14], we reported a difference in the mean OI of infants supported by NAVA compared to ACV was greater than 3 with a standard deviation of the infants' results being 2. We had also reported a difference of 3 in previous studies of PAV [6,8].…”
Section: Sample Sizementioning
confidence: 71%
“…The results of short-term studies [5][6][7][8][9][10][11][12][13][14][15] suggest that both PAV and NAVA improved oxygenation and were associated with lower airway pressures compared to conventional or other triggered modes of ventilation in prematurely born infants with evolving BPD, otherwise known as chronic pulmonary insufficiency of prematurity (CPIP) [16]. There are no studies in that population comparing PAV and NAVA, and hence the aim of this study was to compare the effect of PAV and NAVA on the oxygenation index in infants with evolving or established BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Залежність від кисню також була нижчою (FiO 2 0,36 vs 0,45; Рисунок 4. Порівняльний аналіз впливу режиму PRVC на зміни індексу RI на 2-й та 3-й день спостереження p = 0,007), але це дослідження так само проводилось у недоношених малюків 22-27 тижнів гестації [49]. Кокранівський метааналіз досліджень NAVA в новонароджених, проведений Rossor T. E. et al (2017), не дав остаточної відповіді на питання щодо впливу NAVA на мозкову перфузію та наслідки лікування ГІЕ у вигляді церебральної лейкомаляції [50].…”
Section: український журнал серцево-судинної хірургії 2019unclassified
“…Oksigen dalam bentuk O2 dihasilkan dari air. Gas oksigen digunakan pada proses respirasi oleh hampir semua makhluk hidup (194)(195)(196) .…”
Section: Karakteristik Atom Penyusun Dan Ion 341 Magnesiumunclassified